IMPROVING STUDENTS’ LEARNING OUTCOMES IN INTEGRATED THEMATIC LEARNING USING THINK PAIR SHARE AS COOPERATIVE LEARNING MODEL AT CLASS V OF SDN 09 MANGGIS GANTING IN BUKITTINGGI - Fadhilla Hidayati; Mai Sri Lena (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper is armed with research problems regarding integrated thematic learning that takes place among the fifth-grade students of SDN 09 Manggis Ganting, which comes from teacher-centered, the lack of student skill in using critical thinking to solve problems, the lack of students’ learning activities, the lack of students’ courage to express their opinions, and the low of students’ learning outcome. The purpose of the research is to show how the cooperative learning model of the Think Pair Share can encourage the improvement of fifth-grade students’ learning outcomes at SDN 09 Manggis Ganting of Bukittinggi. Classroom Action Research is type of research in this paper by combining qualitative and quantitative research methods. The research involved educators and 24 fifth-grade students. There are two cycles of research. Two meetings were held in cycle I and one meeting was held in cycle II. The research results indicate that there are increasing percentages in the cycle, which are a) RPP in cycle I at 86.10% (B) and in cycle II at 94.44% (SB), b) the implementation process of the educator aspects in cycle I at 80% (B) and in cycle II at 95% (SB), while the implementation of student aspects in cycle I at 80% (B) and in cycle II at 95% (SB), c) students’ evaluation to encourage an increasing learning outcome in cycle I at 78.25 and in cycle II at 90.47. It can be concluded that the TPS model can encourage increased student learning outcomes.